Talleres para el desarrollo viso motor en niños y niñas de 4 a 5 años de Educación Inicial. - Cordero Avila, Gloria Esperanza (2022)
The diagnosis made on "Dynamic Balance as a means of developing Gross Motor in children of Initial Education" by Casa and Pilataxi (2022) determines the insufficiency in motor development processes due to the virtuality that the educational system faced as a result of the COVID-19 pandemic. The research is based on a mixed approach, based on the inductive and deductive method, the techniques used are observation and field visits with the respective instruments such as observation guide and field record. From this context arises the need to develop a Workshop Guide for visual motor development in infants of initial education with the theme, "Discovering my curious and creative hands" applied in the Marco Aurelio Subía Battle of Panupali Educational Unit that aims to strengthen visual-motor development in boys and girls from 4 to 5 years of age in Early Childhood Education through eight workshops that will contribute to motor skills in the Expression and Communication axis and in the area of ​​Body Expression and Motor Skills proposed by the Initial Education curriculum of the Ecuador of 2014.